Analisa Pelaksanaan Pemberian Bantuan Hukum dalam Perkara Perceraian di Pengadilan Negeri Pekanbaru - Batu, Debora Angela Lumban; Ismi, Hayatul; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Legal assistance is the constitutional right of every citizen to guarantee legal protection andguarantee equality before the law regulated in the law, especially for the underprivileged. But in reality,the implementation of the provision of legal assistance in divorce cases for the underprivileged in thePekanbaru District Court has not been effective in accordance with what is regulated by the law. Thepurpose of this study was to determine the stages of providing legal aid in divorce cases in the PekanbaruDistrict Court, to find out the obstacles in the implementation of providing legal assistance in divorcecases in the Pekanbaru District Court and to find out the efforts made in overcoming obstacles in theimplementation of legal assistance in cases divorce at Pekanbaru District Court.This type of research can be classified as sociological, because in this study the author directlyconducts research on the location or place studied in order to provide a complete and clear picture of theproblem under study. This research was conducted at the Pekanbaru District Court Legal Aid Post, whilethe population and sample were all parties related to the problem under study in this study, data sourcesused primary data, secondary data, and tertiary data, data collection techniques in this study interviewand literature study.From the results of the study can be concluded three things. First, the stages of theimplementation of providing legal assistance in divorce cases at the Pekanbaru District Court are thesame as other civil cases. Second, in the implementation of providing legal assistance in cases of divorce,there are a number of obstacles. Third, there is an effort to overcome obstacles to the implementation ofproviding legal assistance in divorce cases in the Pekanbaru District Court. Suggestion, first the legalaid service provider further enhances the socialization of the stages of providing assistance to theunderprivileged through counseling. Second, the government should pay more attention to the budgetallocation for legal aid services in the Pekanbaru District Court.